Information retrieval with comparing two matching algorithms: A thesis supervisor system case study / Siti Nurhanis Mohd Shekri - Mohd Shekri, Siti Nurhanis (2014)
Final year project is one of the most important subjects that must be taken by Computer Science students. This subject will improve the skills and knowledge of students during their studies at the university. To come up with the excellent result on final year project, the students must to be under a good supervisor. A good supervisor is someone who will cooperate well with the students and give the guide for the students to complete their project. Nmmally, each student at university must find a lecturer to become their supervisor manually. They must approach the lecturer personally to ask them to become their supervisor. This will be a waste of time and energy for students to search each of the lecturers to become a supervisor. In this research will focus on searching the lecturer based on the expertise area of the lecturer. This system will implement the two testing algorithm with information retrieval technique to search an appropriate supervisors for the students. The outcome of this implementation system will suggest the lecturers based on what the students choose as area of expertise. Besides that, this system also enables lecturers to update their information if there are any changes on it. This system will focused on students in Degree of Computer Science only. This is because, they have difficulty to choose lecturers as their supervisor and this system will help them to overcome with that problem.